FORMULATION AND STABILITY STUDY OF DETAM I SOYBEAN VARIETY (GLYCINE MAX (L.) MERR.) EFFERVESCENT GRANULES WITH DIFFERENT TYPE OF EFFERVESCENT AGENTS - Aditya Trias Pradana; Christentia Steffany; Rika Yulia (Acta Pharmaceutica Indonesia, 2021)
The research was conducted to analyze the effect of different types and concentrations of the acid source on the physical characteristics and chemical stability of black soybean (Glycine max (L.) Merr.) Detam I variety effervescent granules. Effervescent granules were made in three different acid sources, which are  15% citric acid for formula I, a mixture of 5% citric acid and 10% tartaric acid for formula II and a mixture of 8% citric acid and 16% tartaric acid for formula III, respectively. The granules’ physical characteristics were obtained by particle size distribution, specific density, bulk density, moisture content, flow time, angle of repose, and effervescent time. Total phenolic content was evaluated for 28 days and the samples were collected at 0, 1, 4, 7, 14, 21, and 28 days. The sample was then measured using a visible spectrophotometric method at 505.5 nm wavelength. The results showed that granule effervescent with formula III was selected as the best formula in all parameters measured, except on the particle size distribution result. In addition,  total phenolic in the formula I was the highest content with a better stability profile, compared to formula II and III. It showed that the formula with a combination of 8% citric acid: 16% tartaric acid is the most optimum formula physically, even for further research, adsorbent use or binder ratio in the formula, and moisture resistant of the primary packaging must also be considered.